Experiences of a dual system: motivation for teachers to study special education. Issue 5 (20th October 2021) - Lindqvist, Henrik; Thornberg, Robert; Lindqvist, Gunilla
ABSTRACT: Special educators are considered essential in schools, both in the regular system and in the separate special needs system. It is important to understand how special education is envisioned among teachers who choose further study in this field. The aim of this study is to gain more knowledge about what motivates teachers to gain further qualifications to become special educators. The study is based on 158 written self-reports from students studying special education. These reports were analysed using thematic analysis. The findings reveal six themes: 'Thirst for knowledge, tools and science', 'Achieving better results as a teacher', 'Improving career opportunities', 'Getting away: giving up teaching in a classroom setting', 'Influence: helping pupils and teachers' and 'Developing schools: identifying deficits in schools' ways of working with special needs education'. These themes are discussed in relation to special educators' work, their jurisdictional control and how their reasons relate to supporting or dismantling the dual system of special education.